Effect of Packaging Materials on Paddy (Oryza sativa) Seed Quality - J.P. SINHA; H.C.S. NEGI; S.K. JHA; S.K. JAIN; MANOJ VISHWAKARMA (Seed Research, 2026)
Paddy (Oryza sativa L.) is the important staple cereal crop in India and its maintenance of seed quality during storage is an integral part of seed multiplication system. Seeds of five paddy cultivars from kharif 2007 were stored in 5 different types of packaging materials, for a period of 30 months at IARI Regional Station, Karnal, to study the effects of packaging materials on seed quality. Paddy cultivars registered significant differences in storability with respect to packaging materials. HDPE woven sacks were found better for paddy seeds. It was economical than cloth bag or hessian cloth bag. Paddy seeds could be safely stored in HDPE woven sack up to 30 months.